Exploring the inflationary effect of oil price volatility in Africa's oil exporting countries - Sina J. Ogede; Emmanuel O. George; Ibrahim A. Adekunle (African Governance and Development Institute (AGDI), 2020)
A range of explanations had been offered for the apparent change in oil price-inflation relationship outcomes ranging from the possible use of alternate energy sources, change in the structure of output regarding fewer oil intensive sectors and the role of fiscal and monetary in the affected oil-exporting countries. These changes had drawn the attention of stakeholders, government and the society at large to the anecdotal relationship among oil price volatility, inflation, and output in Africa oil-exporting countries. This study leans empirical credence to the impact of oil price volatility on inflation and economic performance in the Africa oil-exporting countries from 1995 through 2017. We employed the Pool Mean Group estimation procedure with the inference drawn at a 5% level of significance. We found that oil price volatility had a negative and significant effect on inflation in Africa oil-exporting countries. The study concluded that oil price volatility had a substantial impact on inflation in the Africa oil-exporting countries. The study, therefore, recommended that Africa oil-exporting countries should adopt precautionary measures to monitor inflation potentials due to different responses of inflation to positive and negative oil price shocks.
Keywords: C33; O55; Q41; 330; Oil Price Volatility; Inflation; Growth Outcomes; Pool Mean Group; Africa